CHECKLIST OF BIVALVIA (MOLLUSCA) IN IRAQ - Hiba Mohammed Jihad (Bulletin of the Iraq Natural History Museum, 2023)
This study presents a comprehensive list ofthe freshwater and marine bivalves distributed in Iraq. A total of 51 species were recorded, and distributed as: 14 freshwater species, and 37 marine species, these species belonging to 25 families, all available remarks on the distribution, taxonomy, and nomenclature of these species were given. This study included the recently collected specimens along with thosepreviously studied and recorded in Iraq.